PENGARUH FORMALIN, DIAZEPAM DAN MINUMAN BERALKOHOL TERHADAP KONSUMSI PAKAN, MINUM DAN BOBOT TUBUH Mus musculus - Saraswati, Tyas Rini; Indraswari, Endah; Nurani, Nurani (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT---Diazepam, formalin and drink which contain alcohol are substances that can be a toxic if they are accumulated  in a body. Drink  that contains alcohol can make someone drunk. Diazepam  is a medicine that calms and  its  function  is  to decrease neuron activity. While  formalin which  is  to used as  food preservation causes metabolism disorder. This aim of this research was to investigate and analyze the physiological aspect of M musculus body after it was treated with diazepam, formalin and drink alcoholic. The research used completely Randomize Design. The animal  that was  in experiment were 16 male M musculus and divided  into 4  treatments and 4 replications. The treatments were P0 (Control), P1 (0.04 mg Diazepam), P2 (100 ppm Formalin), P3 (Drink which contains 4,8% alcohol ). Food and drinking water were ad libitum. The treatments were given daily for 30 days. The data were analyzed with anova. The result  indicated that were not significant for all parameters. So, it was concluded  that 0.04 mg diazepam, 100 ppm  formalin and drink which contains 4,8% alcohol didn’t change the metabolism of M musculus body.  Key words: diazepam, formalin and drink alcoholic